Venus y la Cruz. A propósito de la Copia de pareceres sobre el abuso de las pinturas lascivas, de 1632 - Cécile Vincent-Cassy (Mélanges de la Casa de Velázquez, 2025)
In the summer of 1632, the Dominican Cristóbal de Torres y Motones (1573-1654), preacher to Philip IV after having occupied the same position for his father Philip III, was asked to write his opinion on the question of tolerating nude paintings. This opinion is placed at the beginning of those formulated by the theologians of the universities of Salamanca and Alcalá in the printed work entitled On the abuse of lascivious and dishonest figures and paintings; in which it is shown that it is a mortal sin to paint, sculpt and display them for all to see. In fact, the library of the Hispanic Society of America preserves in manuscript form the opinion issued by another royal preacher, a master of the previous one, and much more famous than him: Fray Hortensio Félix Paravicino. We are interested in the context that preceded and accompanied the drafting of these opinions on a matter of the utmost importance to the world of the Court: collections of mythological nudes, but also religious compositions. The lexicon attempts to define what happens when they are painted (and, to a lesser extent, sculpted), when they are viewed and when they are exhibited. I thus propose an initial study of this pivotal text in the artistic literature of around 1630.